Robotic Surgery - Mamat, Khairul Asri Mohd Ghani (International Journal of Human and Health Sciences (IJHHS), 2024)
Robotic surgery is carried out with the use of a unique set of technologies that include specialised “arms” for holding instruments and a camera, as well as a magnified screen and a console. To operate using the Robotic system, the surgeon makes tiny incisions in the body and inserts miniaturized instruments and a high-definition three- dimensional camera. Then, from a nearby console, the surgeon manipulates those instruments to perform the operation. The Robotic system is like a supercomputer which allows the machine to translate the surgeon’s movements into real-time, allowing for greater precision. The computer translates the surgeon’s movements to the instruments that move exactly as the surgeon moves, inside the body. There are many benefits to having a Robotic-assisted surgery. A Robotic-assisted surgery benefits the patient directly—shorter recovery time, less pain—as well as indirectly—the surgeon has better visualization, leading to a more precise surgery. International Journal of Human and Health Sciences Supplementary Issue 02: 2024 Page: S9